The Capitalized society subjugates the weak: Perspectives; Death of a Salesman - Azam, Azmi (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Death of a Salesman is centered on one man trying to reach the American dream and taking his family along for the ride. Loman's life from beginning to end is a troubling story based on trying to become successful, or at least happy. Throughout their lives, the family encounters many problems and the end result is a tragic death caused by stupidity and the need to succeed. During his life, Willy Loman caused his wife great pain by living a life not realizing what he could and couldn't do. Linda lived sad and pathetic days supporting Willy's unreachable goals. Being brought up in this world caused his children to lose their identity and put their futures in jeopardy. At the end, we certainly realize what are the forces that led Loman towards his death. His society enforces him to embrace death as the possible solution, and society helps him to act like a brute. His family is brutally treated to its doom and uncertainty though he sacrifices himself in the alter of a capitalist society that brutally holds the oppressive guillotine of manipulation, exploitation and profit-making attitude.